Myotonic Dystrophy: From Bench to Bedside - Johnson, Nicholas E.; Heatwole, Chad R. (Seminars in Neurology, 2012)
Myotonic dystrophy type 1 (DM1) and type 2 (DM2) are autosomal dominant disorders classically characterized by muscle weakness, myotonia, and early-onset cataracts. Patients may also experience dysfunction of the heart, brain, gastrointestinal, endocrine, skin, and respiratory systems. The pathogenesis of myotonic dystrophy is related to trinucleotide (DM1) and tetranucleotide (DM2) repeat expansions that produce toxic mutant mRNA with subsequent interference of RNA-splicing mechanisms. Optimal disease management includes symptomatic care, screens for asymptomatic disease, counseling, and a multidisciplinary approach. The authors review the pathogenesis, clinical features, diagnostic tests, and standard management of DM1 and DM2 and outline promising clinical research for patients with these disorders.
Keywords: myotonic dystrophy type 1; myotonic dystrophy type 2; congenital myotonic dystrophy